A d-a type modified carbon nitride photocatalyst and a preparation method and application thereof
Patent Information
- Application Number
- CN202611113058.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-25
- Publication Date
- 2026-10-20
AI Technical Summary
这些方法虽然能够一定程度上改善光吸收和载流子分离效率,但大多仍将海水中的盐离子视为不利因素,缺少对盐离子与光催化剂相互作用的有效利用
(1)通过KSCN/LiCl和CCl4协同调控制备改性氮化碳,提高了氮化碳结构有序性、表面活性位点数量和电子结构可调性;
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalysis technology, specifically to a DA-type modified carbon nitride photocatalyst, its preparation method, and its application. Background Technology
[0002] Photocatalysis is a green catalytic technology driven by solar energy or visible light, with significant application prospects in energy conversion, environmental protection, and green chemical synthesis. For example, photocatalytic water splitting for hydrogen production, CO2 reduction, and photocatalytic synthesis of hydrogen peroxide can all achieve the conversion of solar energy into chemical energy under mild conditions. H2O2, as a clean oxidant, is widely used in disinfection, wastewater treatment, chemical oxidation, and energy conversion. Compared with the traditional anthraquinone method, photocatalytic synthesis of H2O2 has advantages such as mild reaction conditions, low energy consumption, and environmental friendliness. However, existing photocatalytic systems still suffer from limitations such as limited light absorption range, easy recombination of photogenerated electrons and holes, low carrier separation and migration efficiency, and insufficient surface reactivity, which restrict their practical application. Donor-acceptor type organic polymers, or DA-type organic polymers, are typically formed by covalently linking electron donor and electron acceptor units. Due to the rich variety of organic structural units and the high designability of molecular structures, DA-type organic polymers allow for the control of light absorption, band structure, carrier separation efficiency, and charge migration pathways at the molecular level, making them an important material system for enhancing photocatalytic performance. By controlling the polymer's topology, conjugation degree, electron donor and acceptor units, and the types of substituents, the photogenerated carrier separation efficiency can be improved, the reaction energy barrier lowered, and thus the efficiency of photocatalytic synthesis of H₂O₂ improved. However, DA-type organic polymer photocatalysts still face some technical challenges in complex systems such as seawater. Seawater contains Na... + K + Mg 2+ Ca 2+ Cl 2- SO4 2-Various salt ions, including those found in seawater, can affect the surface charge distribution and interfacial mass transfer processes of catalysts, and interact with catalytic active sites, reducing their exposure. Simultaneously, salt ions may influence the migration pathways of photogenerated carriers, leading to increased carrier recombination or decreased reaction selectivity. Furthermore, some metal ions in seawater may promote the decomposition of H2O2, reducing its cumulative concentration. Therefore, the photocatalytic synthesis efficiency of DA-type organic polymers for H2O2 in seawater systems still needs improvement. Currently, researchers mainly address these issues by controlling the chemical structure of organic polymers, constructing isomers, introducing functional substituents, optimizing electron donor and acceptor units, and improving catalyst surface structure to enhance photocatalytic performance. While these methods can improve light absorption and carrier separation efficiency to some extent, most still consider salt ions in seawater as a detrimental factor, lacking effective utilization of the interaction between salt ions and photocatalysts. Therefore, developing a DA-type photocatalytic material with tunable structure, high carrier separation efficiency, adaptability to the complex seawater ion environment, and improved photocatalytic synthesis efficiency for H2O2 is of great significance. Summary of the Invention
[0003] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a DA-type modified carbon nitride photocatalyst, its preparation method and application.
[0004] A method for preparing a DA-type modified carbon nitride photocatalyst includes the following steps: S1. Melamine, KSCN and LiCl are mixed and ground to obtain a reaction mixture; S2. The reaction mixture is placed in a quartz boat and heat-treated under a N2 / CCl4 atmosphere to obtain the precursor. S3. Grind the precursor into powder and wash it with deionized water to obtain modified carbon nitride. S4. Modified carbon nitride and trialdehyde phloroglucinol are added to an organic solvent, mixed, and heated to react and obtain the reaction product. S5. The reaction product was washed sequentially with DMF, ethanol and water to obtain DA-type modified carbon nitride photocatalyst. In step S1, the molar ratio of melamine, KSCN and LiCl is 15:(4-6):(8-12).
[0005] In step S2, the N2 / CCl4 atmosphere is obtained by bubbling nitrogen gas through a container containing liquid carbon tetrachloride, with a nitrogen flow rate of 100-500 sccm.
[0006] In step S2, the heat treatment temperature is 500-550℃ and the heat treatment time is 2-10h. In step S4, the mass ratio of the modified carbon nitride to trialdehyde phloroglucinol is 1:(0.8-1.2).
[0007] In step S4, the organic solvent is one of dimethyl sulfoxide, 1,4-dioxane, and N-methylpyrrolidone.
[0008] In step S4, the heating reaction temperature is 110-140℃, and the reaction time is 24-96 h. A DA-type modified carbon nitride photocatalyst is prepared by the preparation method according to any one of claims 1-6.
[0009] Application of a DA-type carbon nitride photocatalyst in photocatalytic reactions.
[0010] Application of a DA-type carbon nitride photocatalyst in the photocatalytic reaction of H2O2 synthesis in seawater.
[0011] This invention uses melamine as a carbon nitride precursor, performs heat treatment in the presence of KSCN and LiCl, and modulates the carbon nitride structure through a reaction atmosphere formed by N2 carrying CCl4 vapor, thus preparing modified carbon nitride. KSCN and LiCl can form an ion-controlled environment during heat treatment, promoting melamine condensation, structural rearrangement, and ordered growth, which is beneficial for forming modified carbon nitride with higher structural order and more edge active sites. Simultaneously, the CCl4 atmosphere can participate in the regulation of surface and electronic structure during thermal polymerization, giving the obtained modified carbon nitride more suitable defect structures, surface polarity, and charge distribution, providing a reaction basis for the subsequent construction of DA-type structures.
[0012] Furthermore, this invention involves heating modified carbon nitride with trialdehyde-based phloroglucinol in a polar organic solvent. The aldehyde group in the trialdehyde-based phloroglucinol can undergo a Schiff base reaction with the amino or nitrogen-containing active sites on the surface of the modified carbon nitride, allowing the trialdehyde-based phloroglucinol-derived structure to be grafted or anchored onto the surface of the modified carbon nitride framework, thereby constructing a DA-type modified carbon nitride photocatalyst. The modified carbon nitride framework can serve as an electron donor structure, and the trialdehyde-based phloroglucinol-derived structure can serve as an electron acceptor structure. A donor-acceptor type electron transport channel is formed between them, which facilitates the directional migration of photogenerated electrons from the donor unit to the acceptor unit, reduces the probability of photogenerated electron-hole recombination, and improves carrier separation and migration efficiency.
[0013] Compared with ordinary carbon nitride, the DA-type modified carbon nitride photocatalyst prepared in this invention has a more rational electronic structure and interfacial charge transport pathway. After synergistic regulation by KSCN / LiCl and CCl4, the surface active sites and electron distribution of the modified carbon nitride are optimized, enhancing its binding stability with trialdehyde phloroglucinol and preventing the trialdehyde phloroglucinol from existing only through physical adsorption, thereby improving the stability and effectiveness of the DA structure. This structure not only broadens the catalyst's response range to visible light but also accelerates the separation and transfer of photogenerated carriers, improving electron utilization efficiency during the photocatalytic reaction.
[0014] In the seawater system, Na + K + Mg 2+ Ca 2+ Cl - SO4 2- Salt ions can easily affect the surface charge distribution, active site exposure, and interfacial mass transfer processes of catalysts, thereby reducing the efficiency of photocatalytic H2O2 synthesis. This invention modulates the structure of modified carbon nitride to give the catalyst surface more suitable polarity, defect structure, and charge distribution. This allows for regulation of its interaction with salt ions in seawater, reducing the shielding effect of salt ions on active sites, and improving the interfacial charge migration process in complex ionic environments. Therefore, the catalyst can maintain high carrier separation efficiency and photocatalytic activity in seawater systems.
[0015] The present invention has the following beneficial technical effects: (1) Modified carbon nitride was prepared by synergistic regulation of KSCN / LiCl and CCl4, which improved the structural order, number of surface active sites and electronic structure tunability of carbon nitride; (2) By modifying carbon nitride and reacting it with trialdehyde pyrogallol in a Schiff base reaction, a stable DA-type organic polymer catalytic structure was constructed, which enhanced the electronic coupling between the donor and acceptor units. (3) The DA-type structure can promote the separation of photogenerated electrons and holes, reduce the probability of carrier recombination, and improve the electron utilization efficiency in the photocatalysis process; (4) By regulating the surface structure and charge distribution of modified carbon nitride, the interfacial reaction behavior of the catalyst in the seawater ion environment can be improved, which not only weakens the adverse effects of salt ions on active sites and carrier migration, but also promotes the corresponding catalytic efficiency. (5) The catalyst has good photocatalytic activity and stability in seawater system, and is suitable for photocatalytic synthesis of hydrogen peroxide and other reactions in seawater, and has good application prospects. Attached Figure Description
[0016] Figure 1An optical photograph of the DA-type modified carbon nitride photocatalyst prepared in Example 2 of this invention; Figure 2 SEM image of the DA-type modified carbon nitride photocatalyst prepared in Example 2 of this invention; Figure 3 The infrared spectra of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of this invention are shown. Figure 4 Comparison of the UV-Vis absorption spectra of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of this invention; Figure 5 The N 1s high-resolution XPS spectra of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of this invention are shown. Figure 6 This is a comparison diagram of the transient photocurrent response of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of the present invention; Figure 7 This is a comparison of the fluorescence intensity of PHI-TP and CN-TP in seawater and pure water according to the present invention; Figure 8 This is a comparison chart showing the performance of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 in the photocatalytic production of H2O2 in seawater and pure water.
[0017] Figure 9 This is a comparison chart showing the performance of photocatalytic H2O2 production of samples prepared in Examples 1-3 and Comparative Examples 2-4 of this invention. Detailed Implementation
[0018] Example 1: Preparation of DA-type modified carbon nitride photocatalyst S1: Add 15 mmol of melamine, 4 mmol of KSCN and 8 mmol of LiCl to an agate mortar and grind for 20 min to uniformly disperse KSCN and LiCl in the melamine to obtain a reaction mixture.
[0019] S2: Transfer the above reaction mixture to a quartz boat and place the boat in the center of a quartz tube. Purge the quartz tube with N2 for 30 minutes to remove air. Then, pass the N2 through a bubbling flask containing liquid CCl4 to create an N2 / CCl4 atmosphere with N2 carrying CCl4 vapor, controlling the N2 flow rate at 100 sccm. Place the quartz tube in a tube furnace and heat it to 550°C at a rate of 5°C / min, holding it at this temperature for 2 hours under the N2 / CCl4 atmosphere. After the reaction is complete, stop heating and allow it to cool naturally to room temperature under an N2 atmosphere to obtain the precursor.
[0020] S3: Remove the precursor from the quartz boat and grind it into powder using an agate mortar for 20 min; wash the powder with 100 mL of deionized water for 30 min, centrifuge, and repeat the water washing 3 times to remove soluble salts and unreacted impurities; then vacuum dry the solid product at 60 °C for 12 h to obtain modified carbon nitride, denoted as PHI-0.
[0021] S4: Add 0.50g of modified carbon nitride PHI-0 and 0.4g of trialdehyde pyrogallol to a pressure-resistant reaction tube containing 30mL of N-methylpyrrolidone. After ultrasonic dispersion for 10min, continue stirring for 30min to ensure thorough mixing. Seal the reaction tube and place it in an oil bath. Heat the temperature to 110℃ and react for 96h to allow the trialdehyde pyrogallol derivative structure to combine with the modified carbon nitride, thus obtaining the reaction product.
[0022] S5: After the reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was centrifuged, and the resulting solid was washed sequentially with DMF, ethanol, and deionized water. Specifically, the solid was washed three times with 30 mL of DMF each time, three times with 30 mL of ethanol each time, and three times with 30 mL of deionized water each time to remove unreacted trialdehyde phloroglucinol and residual solvent. Finally, the washed solid was vacuum dried at 60 °C for 12 h to obtain the DA-type modified carbon nitride photocatalyst, denoted as PHI-TP-0. Example 2 Preparation of DA-type modified carbon nitride photocatalyst S1: Add 15 mmol of melamine, 5 mmol of KSCN and 10 mmol of LiCl to an agate mortar and grind for 25 min to obtain the reaction mixture.
[0023] S2: Transfer the above reaction mixture to a quartz boat and place the boat in the center of a quartz tube. Purge the quartz tube with N2 for 30 minutes to remove air. Then, pass the N2 through a bubbling flask containing liquid CCl4 to create an N2 / CCl4 atmosphere with N2 carrying CCl4 vapor, controlling the N2 flow rate at 300 sccm. Place the quartz tube in a tube furnace and heat it to 520°C at a rate of 5°C / min, holding it at this temperature for 6 hours under the N2 / CCl4 atmosphere. After the reaction is complete, stop heating and allow it to cool naturally to room temperature under an N2 atmosphere to obtain the precursor.
[0024] S3: Remove the precursor from the quartz boat and grind it into powder using an agate mortar for 20 min; wash the powder with 100 mL of deionized water for 30 min, centrifuge, and repeat the water washing 3 times to remove soluble salts and unreacted impurities; then vacuum dry the solid product at 60 °C for 12 h to obtain modified carbon nitride, denoted as PHI.
[0025] S4: Add 0.50g of modified carbon nitride PHI and 0.5g of trialdehyde phloroglucinol to a pressure-resistant reaction tube containing 30mL of dimethyl sulfoxide. After ultrasonic dispersion for 10min, continue stirring for 30min to ensure thorough mixing. Seal the reaction tube and place it in an oil bath. Heat the mixture to 120℃ and react for 48h to obtain the reaction product.
[0026] S5: After the reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was centrifuged, and the resulting solid was washed sequentially with DMF, ethanol, and deionized water. Specifically, the solid was washed three times with 30 mL of DMF each time, three times with 30 mL of ethanol each time, and three times with 30 mL of deionized water each time to remove unreacted trialdehyde phloroglucinol and residual solvent. Finally, the washed solid was vacuum dried at 60 °C for 12 h to obtain the DA-type modified carbon nitride photocatalyst, denoted as PHI-TP. Example 3 Preparation of DA-type modified carbon nitride photocatalyst S1: Add 15 mmol of melamine, 6 mmol of KSCN and 12 mmol of LiCl to an agate mortar and grind for 30 min to obtain the reaction mixture.
[0027] S2: Transfer the above reaction mixture to a quartz boat and place the boat in the center of a quartz tube. Purge the quartz tube with N2 for 30 minutes to remove air. Then, pass the N2 through a bubbling flask containing liquid CCl4 to create an N2 / CCl4 atmosphere with N2 carrying CCl4 vapor, controlling the N2 flow rate at 500 sccm. Place the quartz tube in a tube furnace and heat it to 500°C at a rate of 5°C / min. Heat-treat at this temperature for 10 hours under the N2 / CCl4 atmosphere. After the reaction is complete, stop heating and allow the mixture to cool naturally to room temperature under an N2 atmosphere to obtain the precursor.
[0028] S3: Remove the precursor from the quartz boat and grind it into powder using an agate mortar for 25 min; wash the powder with 120 mL of deionized water for 20 min, centrifuge, and repeat the water washing 3 times to remove soluble salts and unreacted impurities; then vacuum dry the solid product at 70 °C for 10 h to obtain modified carbon nitride, denoted as PHI-2.
[0029] S4: Add 0.50g of modified carbon nitride PHI-1 and 0.6g of trialdehyde phloroglucinol to a pressure-resistant reaction tube containing 30mL of 1,4-dioxane. After ultrasonic dispersion for 10min, continue stirring for 30min to ensure thorough mixing. Seal the reaction tube and place it in an oil bath. Heat the temperature to 140℃ and react for 24h to obtain the reaction product.
[0030] S5: After the reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was centrifuged, and the resulting solid was washed sequentially with DMF, ethanol, and deionized water. Specifically, the solid was washed three times with 30 mL of DMF each time, three times with 30 mL of ethanol each time, and three times with 30 mL of deionized water each time to remove unreacted trialdehyde phloroglucinol and residual solvent. Finally, the washed solid was vacuum dried at 60 °C for 12 h to obtain the DA-type modified carbon nitride photocatalyst, denoted as PHI-TP-2.
[0031] Comparative Example 1: Preparation of DA-type modified carbon nitride photocatalyst The preparation method of the DA-type modified carbon nitride photocatalyst is basically the same as that in Example 2, except that the preparation methods of steps S1 and S2 are different, as detailed below: S1: Add 15 mmol of melamine to an agate mortar and grind for 25 min to obtain the reaction mixture.
[0032] S2: Transfer the above reaction mixture to a quartz boat and place the quartz boat in the central region of a quartz tube. Place the quartz tube in a tube furnace and heat it to 520°C at a heating rate of 5°C / min under an air atmosphere (flow rate of 300 sccm). Hold the temperature for 6 hours. After the reaction is complete, stop heating and allow it to cool naturally to room temperature under a N2 atmosphere to obtain the precursor.
[0033] S3: Remove the precursor from the quartz boat and grind it into powder using an agate mortar for 20 min; wash the powder with 100 mL of deionized water for 30 min, centrifuge, and repeat the water washing 3 times to remove soluble salts and unreacted impurities; then vacuum dry the solid product at 60 °C for 12 h to obtain modified carbon nitride, denoted as CN.
[0034] S4: Add 0.50g of modified carbon nitride CN and 0.5g of trialdehyde phloroglucinol to a pressure-resistant reaction tube containing 30mL of dimethyl sulfoxide. After ultrasonic dispersion for 10min, continue stirring for 30min to ensure thorough mixing. Seal the reaction tube and place it in an oil bath. Heat the mixture to 120℃ and react for 48h to obtain the reaction product.
[0035] S5: After the reaction was completed, the mixture was naturally cooled to room temperature. The reaction product was centrifuged, and the resulting solid was washed sequentially with DMF, ethanol, and deionized water. Specifically, the solid was washed three times with 30 mL of DMF each time, three times with 30 mL of ethanol each time, and three times with 30 mL of deionized water each time to remove unreacted trialdehyde phloroglucinol and residual solvent. Finally, the washed solid was vacuum dried at 60 °C for 12 h to obtain the DA-type modified carbon nitride photocatalyst, denoted as CN-TP. Comparative Example 2: PHI-N2-TP prepared without a CCl4 atmosphere The preparation method of the catalyst in this comparative example is basically the same as that in Example 2, except that N2 is not bubbled through liquid CCl4 in step S2, but heat treatment is carried out only under an N2 atmosphere. Specifically: S1: Add 15 mmol melamine, 5 mmol KSCN and 10 mmol LiCl to an agate mortar and grind for 25 min to obtain the reaction mixture.
[0036] S2: Transfer the above reaction mixture to a quartz boat and place the quartz boat in the central region of a quartz tube; after purging the quartz tube with N2 for 30 min, control the N2 flow rate at 300 sccm and heat to 520℃ at a heating rate of 5℃ / min, and hold at this temperature for 6 h. After the reaction is complete, stop heating and allow it to cool naturally to room temperature under an N2 atmosphere to obtain the precursor.
[0037] S3: Carbon nitride, denoted as PHI-N2, is obtained by operating according to the steps in S3 of Example 2.
[0038] Subsequently, the catalyst was obtained by following the steps S4-S5 in Example 2, and was designated as PHI-N2-TP.
[0039] Comparative Example 3: PHI-LiCl-TP prepared without the addition of KSCN The preparation method of the catalyst in this comparative example is basically the same as that in Example 2, except that KSCN is not added in step S1, and only melamine and LiCl are used. Specifically: S1: Add 15 mmol of melamine and 10 mmol of LiCl to an agate mortar and grind for 25 min to obtain the reaction mixture.
[0040] Subsequently, modified carbon nitride, denoted as PHI-LiCl, was obtained by following steps S2-S3 in Example 2; finally, a catalyst, denoted as PHI-LiCl-TP, was obtained by following steps S4-S5 in Example 2.
[0041] Comparative Example 4: PHI-KSCN-TP prepared without the addition of LiCl The preparation method of the catalyst in this comparative example is basically the same as that in Example 2, except that LiCl is not added in step S1, and only melamine and KSCN are used. Specifically: S1: Add 15 mmol of melamine and 5 mmol of KSCN to an agate mortar and grind for 25 min to obtain the reaction mixture.
[0042] Subsequently, modified carbon nitride, denoted as PHI-KSCN, was obtained by following steps S2-S3 in Example 2; finally, a catalyst, denoted as PHI-KSCN-TP, was obtained by following steps S4-S5 in Example 2.
[0043] Figure 1 The image shows an optical photograph of PHI-TP, revealing that the DA-type modified carbon nitride photocatalyst PHI-TP prepared in this application is a red powder.
[0044] Figure 2 The image shows a SEM image of PHI-TP, which reveals that PHI-TP has an irregular blocky morphology.
[0045] Figure 3 The infrared spectra of the modified carbon nitrides PHI and CN and the photocatalysts PHI-TP and CN-TP prepared in Example 2 and Comparative Example 1 are shown below. Figure 3 It can be seen that all four catalysts exhibited a range of 300-3600 cm⁻¹. -1 The NH stretching vibration peak, 805 cm⁻¹ -1 The out-of-plane bending peak of heptamethrin is located at 1200-1700 cm⁻¹ -1 The CN heterocyclic peaks between them confirm their basic carbon nitride structure. Furthermore, PHI-TP and CN-TP also exhibit a peak at 1620 cm⁻¹. -1 The C=O vibration peak at the point indicates the keto structure of the TP group after the construction of the DA system, proving the successful construction of the corresponding DA structure.
[0046] Figure 4 The figures show a comparison of the UV-Vis absorption spectra of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of this invention. As can be seen from the figures, each sample exhibits a certain absorption in the UV region, indicating that it possesses the basic photoresponse characteristics of photocatalytic materials. Compared to ordinary carbon nitride or unmodified PHI samples, the PHI-TP sample shows significantly enhanced absorption in the visible light region, with a red shift in the absorption edge. This indicates that the introduction of trialdehyde-based phloroglucinol expands the conjugated structure of the modified carbon nitride, improving its utilization of visible light. This phenomenon is mainly attributed to the formation of a donor-acceptor electronic structure between the PHI backbone and the trialdehyde-based phloroglucinol-derived structure, promoting intramolecular charge transfer and expanding the light absorption range of the catalyst. Stronger visible light absorption facilitates the generation of more photogenerated electrons and holes, providing more reactive charge carriers for the subsequent photocatalytic synthesis of H2O2, thereby improving photocatalytic activity.
[0047] Figure 5The figures show the high-resolution XPS spectra of N 1s of the modified carbon nitride and photocatalyst prepared in Example 2 and Comparative Example 1 of this invention. As can be seen from the figures, the N 1s values of the samples can be fitted into three components: approximately 398.7 eV, 399.8 eV, and 401.1 eV. The peak near 398.7 eV is attributed to hybrid nitrogen with a C=NC structure in the carbon nitride framework, the peak near 399.8 eV is attributed to N-(C)3 structure or bridged nitrogen, and the peak near 401.1 eV is attributed to edge-NH or protonated nitrogen. Compared with PHI, the peak intensities and positions of each nitrogen species in PHI-TP changed, indicating that the introduction of trialdehyde-based phloroglucinol altered the chemical environment of nitrogen atoms on the PHI surface. The change in the framework nitrogen peaks indicates an electronic interaction between PHI and the trialdehyde-based phloroglucinol-derived structure, which is beneficial for the formation of a DA-type modified carbon nitride photocatalyst.
[0048] pass Figure 6 It can be seen that all samples exhibit significant photocurrent responses during the periodic switching on and off of illumination, indicating their ability to generate photogenerated electrons and holes under illumination. Among them, the PHI-TP sample showed the highest photocurrent response intensity, with minimal peak change during multiple switching cycles, indicating good photoresponse capability and photoelectrochemical stability. In contrast, the photocurrent intensities of PHI and other comparative samples were lower, suggesting relatively insufficient photogenerated carrier separation and migration efficiency. The enhanced photocurrent of PHI-TP is mainly attributed to the formation of a DA-type structure between modified carbon nitride and trialdehyde-resorcinol, establishing an effective charge transport channel between the electron donor and acceptor, promoting directional migration of photogenerated electrons, and reducing the electron-hole recombination probability. These results demonstrate that the PHI-TP catalyst prepared in this invention has superior carrier separation efficiency, which is beneficial for improving the photocatalytic synthesis performance of H2O2.
[0049] Figure 7 This is a comparison of the fluorescence intensity of PHI-TP and CN-TP in seawater and pure water. Figure 7 It can be seen that the fluorescence intensity of PHI-TP in seawater is lower than that in pure water, while the fluorescence intensity of CN-TP in seawater is not significantly different from that in pure water. This indicates that PHI-TP has better charge separation ability in seawater.
[0050] pass Figure 8It can be seen that, under O2 atmosphere and in a seawater system (3.5 wt% NaCl), irradiated with a 300W xenon lamp, the H2O2 production of PHI-TP in the seawater system, as determined by cerium sulfate spectrophotometry, was significantly higher than that in the pure water system, being 1.88 times higher. This indicates that salt ions in seawater did not inhibit the photocatalytic reaction; on the contrary, they may have improved the H2O2 production efficiency by adjusting the surface charge distribution of the catalyst, promoting interfacial electron transfer, or improving the oxygen reduction process. Simultaneously, the yield of PHI-TP was significantly higher than that of CN-TP, indicating that the PHI structure regulation and the DA-type structure constructed from trialdehyde resorcinol have a synergistic effect, effectively promoting carrier separation and enhancing the photocatalytic H2O2 production performance.
[0051] pass Figure 9 It can be seen that the synthesis performance of H2O2 by PHI-TP related samples (PHI-TP-0, PHI-TP, PHI-TP-2) is significantly better than that of the corresponding control samples (PHI-N2-TP, PHI-LiCl-TP, PHI-KSCN-TP), indicating that the combined effect of the corresponding preparation conditions has achieved efficient photosynthesis of H2O2 from seawater.
[0052] The PHI-TP catalyst prepared in this application outperforms Comparative Examples 1-4, mainly due to the synergistic regulation of the modified carbon nitride structure by KSCN, LiCl, and CCl4 atmospheres. Comparative Example 1 only obtained CN by heat-treating melamine in air without introducing a KSCN / LiCl ionic thermal environment and CCl4 gas-phase regulation. The resulting CN structure had low orderliness, insufficient nitrogen-containing active sites on its surface, and a weak ability to form an effective DA structure with trialdehyde-based pyrogallol. Therefore, the CN-TP carrier separation efficiency and photocatalytic H2O2 production performance were low. Comparative Example 2, although containing KSCN and LiCl, did not employ a CCl4 atmosphere, lacking the regulation of the relative defect structure, edge sites, and electron distribution by halogen gas, resulting in weakened electronic coupling between PHI-N2 and trialdehyde-based pyrogallol. Comparative Example 3, without the addition of KSCN, struggled to fully promote melamine condensation rearrangement and PHI-type structure formation, resulting in insufficient activity of the obtained PHI-LiCl structure. Comparative Example 4, lacking LiCl and the molten salt-assisted environment, resulted in decreased reaction uniformity and structural ordering. In contrast, in the embodiments of this application, KSCN / LiCl jointly promoted the formation of the PHI structure, and CCl4 further optimized surface defects and charge distribution, enabling PHI and trialdehyde pyrogallol to form a more efficient DA electron transport channel, thereby improving photogenerated carrier separation and interfacial reaction efficiency.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. However, any modifications, alterations, and variations made by those skilled in the art without departing from the scope of the present invention based on the disclosed technical content are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, and variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a DA-type modified carbon nitride photocatalyst, characterized in that, Includes the following steps: S1. Melamine, KSCN and LiCl are mixed and ground to obtain a reaction mixture; S2. The reaction mixture is placed in a quartz boat and heat-treated under a N2 / CCl4 atmosphere to obtain the precursor. S3. Grind the precursor into powder and wash it with deionized water to obtain modified carbon nitride. S4. Modified carbon nitride and trialdehyde phloroglucinol are added to an organic solvent, mixed, and heated to react and obtain the reaction product. S5. The reaction product was washed sequentially with DMF, ethanol and water to obtain DA-type modified carbon nitride photocatalyst.
2. The preparation method of the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S1, the molar ratio of melamine, KSCN and LiCl is 15:(4-6):(8-12).
3. The preparation method of the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S2, the N2 / CCl4 atmosphere is obtained by bubbling nitrogen gas through a container containing liquid carbon tetrachloride, with a nitrogen flow rate of 100-500 sccm.
4. The preparation method of the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S2, the heat treatment temperature is 500-550℃ and the heat treatment time is 2-10h.
5. The method for preparing the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S4, the mass ratio of the modified carbon nitride to trialdehyde phloroglucinol is 1:(0.8-1.2).
6. The method for preparing the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S4, the organic solvent is one of dimethyl sulfoxide, 1,4-dioxane, and N-methylpyrrolidone.
7. The method for preparing the DA-type modified carbon nitride photocatalyst according to claim 1, characterized in that, In step S4, the heating reaction temperature is 110-140℃, and the reaction time is 24-96h.
8. A DA-type modified carbon nitride photocatalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
9. The application of the DA-type carbon nitride photocatalyst according to claim 7 in photocatalytic reactions.
10. The application of the DA-type carbon nitride photocatalyst according to claim 7 in the photocatalytic reaction of seawater photosynthesis of H2O2.